A Class of Enhanced Capacity Secure Steganographic Systems Based On LSB Insertion Technique - Ling , Huo Chong (2002)
Steganography is a way to hide secret message inside an innocent media such that only the receiver knows the existence of the message. The main goal is thus to avoid suspicion to the message hidden inside the innocent media. One of the most common techniques used is steganography is the least significant bit (LSB) insertion. In this thesis, we propose a secure steganographic system based on LSB insertion technique.It has an enhanced embedding capacity and employs a combination of feature from compression algorithms, hashing algorithms, and private and public key cryptography.